Increasing Application for Marriage Dispensation during the COVID-19 Pandemic in the Sociology Review of Law at the Jombang Religious Court - Rahayu Hartini; Jamik Imam Utomo (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
This paper discusses the increasing application for Marriage Dispensation during the corona virus pandemic which is viewed from the sociological aspect of law. Applications for dispensation for marriage are more complicated and must be submitted through the Religious Courts, but the facts on the ground show that the number of applications for dispensation for marriage is increasing during this pandemic. The situation during this pandemic which makes sociological factors, the occurrence of imbalances in the structure of society makes the dysfunction of the community's inability to maintain their nature. The legal issues are: (1) What are the factors that increase the number of applications for a marriage dispensation in the Jombang Religious Courts (2) What are the considerations of the Jombang Religious Court judges in granting the marriage dispensation. This research is juridical and sociological in Jombang Religious Court. By using a statue approach, conceptual, with primary and secondary data types and analyzed descriptively qualitatively. The discussion of the research results shows that: 1). The increasing application for Marriage Dispensation during this pandemic is caused by the association of children with restrictions on learning activities so that their time is used more for playing gadgets that are not common and the lack of parental supervision, this makes many factors that can plunge them. 2). The basis of the judge's consideration in granting the application for dispensation for marriage is based on "benefit and harm" then the court will grant the request for dispensation. Because it is feared that if they are not married, they will increase sin and disrupt the legal rights of children who are born under the law.Keywords: Application; Marriage Dispensation; Pandemic; Sociology of Law; Religious Courts AbstrakTulisan ini membahas tentang meningkatnya permohonan Dispensasi Perkawinan pada masa pandemi virus corona ditinjau dari aspek sosiologis hukum. Permohonan dispensasi nikah memang lebih rumit dan harus diajukan melalui Pengadilan Agama, namun fakta di lapangan menunjukkan jumlah permohonan dispensasi nikah semakin meningkat di masa pandemi ini. Situasi di masa pandemi ini yang menjadikan faktor sosiologis, terjadinya ketidakseimbangan dalam struktur masyarakat menjadikan disfungsi ketidakmampuan masyarakat dalam menjaga kodratnya. Permasalahan hukum tersebut adalah: (1) Faktor-faktor apa sajakah yang menyebabkan meningkatnya jumlah permohonan dispensasi nikah di Pengadilan Agama Jombang (2) Apa saja pertimbangan hakim Pengadilan Agama Jombang dalam memberikan dispensasi nikah. Penelitian ini bersifat yuridis dan sosiologis di Pengadilan Agama Jombang. Dengan menggunakan pendekatan patung, konseptual, dengan jenis data primer dan sekunder serta dianalisis secara deskriptif kualitatif. Pembahasan hasil penelitian menunjukkan bahwa: 1). Meningkatnya permohonan Dispensasi Nikah di masa pandemi ini disebabkan oleh pergaulan anak dengan pembatasan kegiatan belajar sehingga waktunya lebih banyak digunakan untuk bermain gadget yang tidak lazim dan kurangnya pengawasan orang tua, hal ini menjadikan banyak faktor yang dapat menjerumuskan mereka. 2). Dasar pertimbangan hakim dalam mengabulkan permohonan dispensasi perkawinan didasarkan pada “manfaat dan kerugian” maka pengadilan akan mengabulkan permohonan dispensasi. Karena dikhawatirkan jika tidak menikah akan menambah dosa dan mengganggu hak-hak hukum anak yang lahir di bawah hukum.Kata Kunci: Penerapan, Dispensasi Perkawinan, Pandemi, Sosiologi Hukum, Peradilan Agama.